Spontaneous solar water splitting by DSSC/CIGS tandem solar cells - Chae, Sang Youn; Park, Se Jin; Joo, Oh-Shim; Min, Byoung Koun; Hwang, Yun Jeong (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
A tandem solar cell equipped with a dye-sensitized solar cell (DSSC) and a Culn(x)Ga(1-x)S(y)Se(1-y) (CIGS) bottom sub-cell was assessed for photovoltaic cell (PV)-assisted water splitting application. Two types of cobalt complexes ([Co(bpy)(3)](2+/3+) and [Co(phen)(3)](2+/3+)) were tested as the redox couples in the DSSC sub-cell. Of these, [Co(phen)(3)](2+/3)+ showed a larger open circuit potential and higher power conversion efficiency for the DSSC/CIGS tandem cell with high stability due to its more positive redox potential. Two unit cells of the DSSC/CIGS tandem cell were assembled as a module to supply sufficient power for water electrolysis. Spontaneous solar water splitting was realized when the DSSC/CIGS module was connected to a stainless steel anode and a platinum cathode. The [Co(phen)(3)](2+/3+) redox couple in the tandem cell was found to have high solar to hydrogen conversion efficiency (eta(STH) = 4.65%) in the PV-assisted electrolysis cell. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: REDOX COUPLES; EFFICIENCY